Toxicological evaluation of dried Kacangma Herb (Leonurussibiricus)in rats - Chua, Hun Pin; Aminah Abdullah; Murugaiyah M. (Universiti Kebangsaan Malaysia, 2009)
Kacangma (Leonurus sibiricus L.) is a popular traditional herb that has been consumed for decades by the people of Sarawak as a herbal medicine or culinary ingredient. The toxicity of dried kacangma herb on Sprague Dawley male and female rats was evaluated through 90-day sub-chronic studies. The rats were fed kacangma at the rate of 0.5 (low dose), 5 (medium dose) and 25 (high dose) g/kg body weight. The control groups of rats received only the commercial rat pellet. Minor treatment-related effects were observed for body weights, organ weights and the lipid profile parameters and these did not appear to be of toxicological significance. In the sub-chronic toxicity studies, some indications of renal and liver toxicity were evident in the medium and high dose groups when plasma creatinine and liver enzymes were found to be higher when compared with the control and the low dose groups. The hematology study reveals statistically significant mild anemia in rats from the medium and high dose groups as indicated by decreases in hemoglobin, red blood cell count and packed cell volume (hematocrit value). Administration of kacangma herb at medium and high dose was also found to cause adverse effects in histopathological structure of the liver and kidney of both male and female rats. However, low dose group showed no significant differences compared to the control. Therefore, it is considered safe and less chance of developing toxicity if the herb is consumed at the dose of 0.5 g/kg body weight as observed throughout the 90 days period of sub-chronic study.